Client Conservatism and Auditor-Client Contracting - DeFond, Mark L.; Lim, Chee Yeow; Zang, Yoonseok (The Accounting Review, 2016)
ABSTRACT We find that auditors of more conservative clients charge lower fees, issue fewer going concern opinions, and resign less frequently, consistent with more conservative clients imposing less engagement risk on their auditors. Using path analysis, we find evidence that both inherent risk and auditor business risk explain these associations. Also consistent with conservatism reducing auditor business risk, we find that client conservatism is associated with fewer lawsuits against auditors and with fewer client restatements. Taken together, our results are consistent with auditors viewing client conservatism as an important determinant of engagement risk that, in turn, affects auditor-client contracting decisions. Our findings should be of interest to auditors who actively manage client risk and to standard-setters who recently dropped conservatism as a desired attribute of financial reporting quality. Data Availability: All data are publicly available from sources indicated in the text.